2014
DOI: 10.1007/s11056-014-9463-3
|View full text |Cite
|
Sign up to set email alerts
|

Early performance of planted hybrid larch: effects of mechanical site preparation and planting depth

Abstract: Some site preparation is generally recommended to enhance the growth and survival of planted and naturally regenerated seedlings, but must be justified both economically and environmentally. More severe preparation is thought to be necessary for intensive plantation silviculture, e.g., using fast-growing, ameliorated stocks, especially in boreal ecosystems. Although not justified scientifically, deep-planting of seedlings is often 2 discouraged and may even be financially penalized in eastern Canada. We thus e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 50 publications
4
17
0
Order By: Relevance
“…of early growth of hybrid larch (Larix 9 marschlinsii Coaz) seedlings over two growing seasons following planting demonstrated that trenching (simple and double), mounding and inverting site preparation resulted in undistinguishable growth performance (Buitrago et al, 2015). This observation led to the conclusion that simple trenching represents the most economically attractive silvicultural practice for early growth of hybrid larch.…”
Section: Monitoringmentioning
confidence: 99%
See 3 more Smart Citations
“…of early growth of hybrid larch (Larix 9 marschlinsii Coaz) seedlings over two growing seasons following planting demonstrated that trenching (simple and double), mounding and inverting site preparation resulted in undistinguishable growth performance (Buitrago et al, 2015). This observation led to the conclusion that simple trenching represents the most economically attractive silvicultural practice for early growth of hybrid larch.…”
Section: Monitoringmentioning
confidence: 99%
“…), red maple (Acer rubrum L.) and black spruce (Picea mariana (Mill.) BSP) was harvested in 2009 (clear-cut with 5% retention) prior to the installation of an experiment to investigate the impact of different MSP techniques on the growth performance of hybrid larch planted in April 2010 (Buitrago et al, 2015). The experimental design consisted of a complete block design comprising three replicated blocks (Fig.…”
Section: Sampling Sitementioning
confidence: 99%
See 2 more Smart Citations
“…(i) To ensure that fast-growing trees can achieve their full potential without using herbicides, which are banned in Quebec in forestry operations, through employing site-preparation techniques such as trenching and mounding (Bilodeau-Gauthier et al 2011;Buitrago et al 2015). These techniques create a heterogeneous microtopography that could provide habitat for vascular understory plant species (Haeussler et al 1999;Ramovs and Roberts 2003), as well as hatching habitat for amphibians (Semlitsch et al 2009).…”
Section: Some Examples Of Novel Stand-level Managementmentioning
confidence: 99%